Vertical cup/disc ratio in relation to optic disc size: its value in the assessment of the glaucoma suspect. Issue 10 (1st October 1998) - Garway-Heath, David F; Ruben, Simon T; Viswanathan, Ananth; Hitchings, Roger A
Abstract : AIMS: The vertical cup/disc ratio (CDR) has long been used in the assessment of the glaucoma suspect, though the wide range of CDR values in the normal population limits its use. Cup size is related physiologically to disc size and pathologically to glaucomatous damage. Disc size can be measured at the slit lamp as the vertical disc diameter (DD). The ability of the CDR, in relation to DD, to identify glaucomatous optic discs was investigated. METHODS: 88 normal, 53 early glaucoma, and 59 ocular hypertensive subjects underwent stereoscopic optic disc photography and clinical biometry. Photographs were analysed in a masked fashion by computer assisted planimetry. The relation between vertical cup diameter and DD was explored by linear regression, and expressed in terms of CDR. The upper limit of normal was defined by the 95% prediction intervals of this regression (method 1) and by the upper 97.5 percentile for CDR (method 2). The sensitivity and specificity of CDR to identify an optic disc as glaucomatous was tested with these disc size dependent and disc size independent cut offs in small, medium, and large discs. RESULTS: The CDR was related to DD by the equation CDR = (−1.31 + (1.194 × DD))/DD. The sensitivity in small, medium, and large discs was 80%, 60%, and 38% respectively for method 1 and 33%, 67%, and 63% respectively for method 2. Specificity was 98.9% (method 1) and 97.7% (method 2). CONCLUSIONS: The CDR, relative to disc size, is useful clinically, especially to assist in identifying small glaucomatous discs.